Instruments of Power. The affective power of sound design in American music education - Noah Karvelis; Thomas S. Popkewitz (Cadernos de História da Educação, 2023)
Music education in the United States has increasingly focused upon student creativity and practices such as improvisation. While such practices and changes are often conceptualized as flexible, inclusive reforms about making kinds of children, historically the curriculum has little to do with music and is instead concerned with taming uncertainty in the governing of child.   We examine the Orff-Schulwerk pedagogy in the teaching of music, thought of as a progressive reform which emphasized improvisation and creativity. Exploring briefly Orff-Schulwerk’s production in the Weimar Republic as it travels and translated into the post-war United States, we consider the curriculum as formed through psychological research about rationality, choice, and creativity. The focus is on the system of reasoning embodied in the curriculum as generating principles about desired kind of persons in a stable, secure future related to salvation narratives- principles different in the Weimar Republic and US. The shifting design of people in Orff-Schulwerk curriculum and classroom instruments for learning of sound are, we argue, practices in governing of the body and soul. The fabricating and mapping in the music curriculum is about kinds of populations required as evidence of the progressive desires that simultaneously distributes differences.